(untitled) (Journal of Information Technologies in Education (ITE), 2009)
Analysis of existing systems for control of Grid jobs is given. Testing of three systems (LAP, P_GRADE, BIOSYMGRID) were performed on the grid-resource of National Taras Shevchenko University of Kyiv. Comparison of tested systems is given. Requirements to the atrchictecture of complex web-oriented system of virtual laboratories in Grid-infrastructure for scientific and educational institutions of Ukraine were developped.